Active backers, product commercialisation and product quality after a crowdfunding campaign: A comparison between first-time and repeated entrepreneurs. (March 2020) - Butticè, Vincenzo; Noonan, Douglas
Building on the theories of social capital and social obligation, we study how the attraction of active backers, that is, backers who participate in the co-design of the product is associated with product commercialisation and product quality after a reward-based crowdfunding campaign. We argue theoretically and show empirically that this association varies when the entrepreneur's experience in conducting crowdfunding campaign is taken into account. Through a quantitative analysis of 1406 board games campaigns posted on Kickstarter, we show that for entrepreneurs who are novice to crowdfunding, attracting a large crowd of active backers increases the chances to commercialise the product after the campaign, while it reduces its final quality. On the contrary, for entrepreneurs who already relied on crowdfunding in the past, the attraction of a large crowd of active backers is associated with increasing product quality.